Training on Using White Turmeric to Make Noodles in Argorejo Village, Yogyakarta - Enjelora Uri Palinggi; Ichlasia Ainul Fitri (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2023)
Empon-empon plants such as white turmeric are plants that grow widely in Indonesia. One of the areas producing white turmeric is Argorejo Village, Yogyakarta. In this village, white turmeric is only used fresh, and a small portion is processed into herbal drinks which have a short shelf life. Previously, there has been a lot of research regarding the benefits of empon-empon, especially white turmeric, as anti-diabetic and anti-tumor because of its high antioxidant content. The results of this research show the importance of consuming white turmeric. The use of white turmeric can be innovated into functional food products such as noodles, which are people's favorite food. The aim of this community service is to train and practice how to develop white turmeric noodle products in the Argorejo Village environment. The activity stages included counseling by students from the Faculty of Agroindustry, which was attended by more than 20 participants, followed by training activities on making white turmeric noodles, and closed with sensory testing to determine the community's acceptance. The public is enthusiastic about participating in this series of programs and understands that the product has sales value and has good market potential.